2011
DOI: 10.1098/rsbl.2011.0726
|View full text |Cite
|
Sign up to set email alerts
|

Corvids can decide if a future exchange is worth waiting for

Abstract: Evidence for time-dependent calculations about future rewards is scarce in non-human animals. In non-human primates, only great apes are comparable with humans. Still, some species wait for several minutes to obtain a better reward in delayed exchange tasks. Corvids have been shown to match with non-human primates in some time-related tasks. Here, we investigate a delay of gratification in two corvid species, the carrion crow (Corvus corone) and the common raven (Corvus corax), in an exchange task. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
131
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(143 citation statements)
references
References 24 publications
11
131
1
Order By: Relevance
“…The superior performance of primates in DGTs was recently challenged by Dufour et al [12], who showed that corvids can wait up to 5 min in a qualitative exchange DGT. Common ravens (Corvus corax) and carrion crows (Corvus corone) waited longer if the disproportion in value was large, and when they renounced waiting they tended to do so instantly rather than in the middle of the delay [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superior performance of primates in DGTs was recently challenged by Dufour et al [12], who showed that corvids can wait up to 5 min in a qualitative exchange DGT. Common ravens (Corvus corax) and carrion crows (Corvus corone) waited longer if the disproportion in value was large, and when they renounced waiting they tended to do so instantly rather than in the middle of the delay [12].…”
Section: Introductionmentioning
confidence: 99%
“…Common ravens (Corvus corax) and carrion crows (Corvus corone) waited longer if the disproportion in value was large, and when they renounced waiting they tended to do so instantly rather than in the middle of the delay [12]. During longer delays, subjects temporarily deposited food before returning it, suggesting that their inhibition control was facilitated through being food hoarders [12]. Interestingly, the same crows failed to wait for higher quantities in an exchange DGT, despite choosing higher quantities in a binary preference test [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the early research with pigeons and rats indicated that animals showed little or no self-control, often discounting future rewards even on a scale of a few seconds (see Logue, 1988). However, using new tests such as the accumulation task, as well as tasks that make use of food exchanges to obtain delayed, more valuable rewards (e.g., Beran, Rossettie, & Parrish, 2016;Dufour, Pelé, Sterck, & Thierry, 2007;Dufour, Wascher, Braun, Miller, & Bugnyar, 2012;Pelé, Dufour, Micheletta, & Thierry, 2010), or tasks that require animals to move farther to obtain better rewards (e.g., Stevens, Hallinan, & Hauser, 2005), or tasks that substitute tokens for food rewards (e.g., Jackson & Hackenberg, 1996;Judge & Essler, 2013), indicate that animals sometimes do show self-control and can delay gratification. In addition, varying aspects of experimental design shows that some species that normally are impulsive will make use of opportunities to force themselves to choose the later reward (Ainslie, 1974;Grosch & Neuringer, 1981;Rachlin & Green, 1972).…”
Section: Dealing With Fallibility: Strategic Delay Of Gratificationmentioning
confidence: 99%
“…Furthermore, because food motivation is 119 known to influence problem-solving behaviour (Laland & Reader, 1999; Sol, Griffin & Bartomeus, 120 2012;Griffin, Diquelou & Perea, 2014;Griffin & Guez, 2014), we tested subjects early in the 121 5 morning without feeding them the evening prior to the test. Finally, as food motivation is influenced 122 by food quality (Fontenot et al, 2007;Dufour et al, 2012;Hillemann et al, 2014); we used high 123 value food (based on a previously performed preference test) for testing (Rao, et al in press). 124…”
Section: Introduction 23mentioning
confidence: 99%